Veja o que a Veja fez: o jogo de ocultamento dos jovens nas manifestações de 1992 - Santos, Claitonei de Siqueira (2020)
The present work is linked to the line of research entitled “State, Policies and History of Education” of the Graduate Program of the Faculty of Education of the Federal University of Goiás. It seeks to understand how Veja magazine approached youth and youth, in his coverage of the political crisis of 1992, which culminated in the movements of streets and squares calling for the impeachment of President Fernando Collor de Melo. The thesis starts from Pierre Bourdieu's conception that it is necessary to understand young people from the social context in which they are inserted, because the criteria that define youth are always external and, because of this characteristic, subject to manipulation. Hence the attempts to conceal the youths in the reports about the protests against the president in 1992, aiming to serve the interests of classes linked to Veja magazine. The qualitative research had as its documentary corpus the analysis of the journalistic text and the photographs of eight editions that contain reports made by Veja magazine, about the actions of young people in the 1992 Impeachment movement, both from the perspective of Bourdieu (2019, 2007, 1996, 1997) and Burke (1994). The results show that the journalistic language, used in the reports, produced the de-characterization and concealment of young people in the 1992 movements, according to the class interests linked to Veja. Veja magazine develops an invisible censorship process that, depending on the interests at stake, hides by showing and imputing the images used on protesting young people, called students, as a major factor in the departure of President Fernando Collor, without this and the class interests linked to the magazine are made explicit in the texts of the reports.